UNIVERSITY AS A CENTER OF INNOVATION: METHODOLOGICAL ASPECTS - M. B. Melekhina (Высшее образование в России)
The article considers the basic positions of the target model of the development of Ukhta State Technical University for the period up to 2025, outlines the strategic initiatives that contribute to the status of a University as “the space of innovation”. The author emphasizes the role of the third stage of higher education (post-graduate) and teaching schools in generating innovative activity of the University.